2018
DOI: 10.3389/fimmu.2018.02398
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Dopamine Controlled by Gut Microbes Inhibits Invariant Natural Killer T Cell-Mediated Hepatitis

Abstract: Neurotransmitters have been shown to regulate immune responses, and thereby are critically related to autoimmune diseases. Here we showed that depletion of dopaminergic neurons significantly promoted activation of hepatic iNKT cells and augmented concanavalin A (Con A)-induced liver injury. The suppressive effect of dopamine on iNKT cells was mediated by D1-like receptor-PKA pathway. Clearance of gut microbiota by antibiotic cocktail reduced synthesis of dopamine in intestines and exacerbated liver damage, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 50 publications
0
56
0
1
Order By: Relevance
“…Concerning DA, this is further confirmed by the high levels of tyrosine hydroxylase found in the small intestine [140]. Moreover, antibiotics-induced gut microbiota depletion decreases intestinal DA synthesis in mice [141] and GF mice show unequal brain mRNA expression of DA D1 receptor (D1R), being upregulated within the hippocampus and reduced at dorsal and ventral striatum level [1]. Hence, DA metabolism is drastically affected by the alteration of microbiota ecosystem.…”
Section: N-3 Pufas Serotonin Dopamine and Npdsmentioning
confidence: 85%
“…Concerning DA, this is further confirmed by the high levels of tyrosine hydroxylase found in the small intestine [140]. Moreover, antibiotics-induced gut microbiota depletion decreases intestinal DA synthesis in mice [141] and GF mice show unequal brain mRNA expression of DA D1 receptor (D1R), being upregulated within the hippocampus and reduced at dorsal and ventral striatum level [1]. Hence, DA metabolism is drastically affected by the alteration of microbiota ecosystem.…”
Section: N-3 Pufas Serotonin Dopamine and Npdsmentioning
confidence: 85%
“…Vitamin B6 depletion in AIMD may affect the metabolism of catecholamines, including L-dopa, dopamine, noradrenaline, and adrenaline, which are major neurotransmitters associated with the regulation of arousal. About half of the total peripheral dopamine is produced in the intestinal tract, and the levels of this metabolite are reduced under the AIMD condition 31,32 . Moreover, increased amounts of the inhibitory neurotransmitters GABA and glycine were observed under the AIMD condition.…”
Section: Discussionmentioning
confidence: 99%
“…A regulatory axis from the gut microbes to neurotransmitter and then to autoimmune system was proposed in both rodents and humans (Tognini, 2017 ). Xue et al ( 2018 ) showed that depletion of dopaminergic neurons significantly promoted activation of mice hepatic iNKT cells and augmented concanavalin A-induced liver injury by D1-like receptor-PKA pathway in mice. In the present study, expression of the genes in IGF-1/DAF-16 signaling ( age-1 and daf-16 ) and innate immune signaling pathways ( pmk-1 and sek-1 ) was significantly down-regulated in the mutant defective in cat-2 , and supplementation of dopamine to mutant cat-2 restored the expression of these genes to the level in the WT.…”
Section: Discussionmentioning
confidence: 99%